Photoelectron emission from lithiated diamond. Issue 10 (14th August 2014) - O'Donnell, Kane M.; Martin, Tomas L.; Edmonds, Mark T.; Tadich, Anton; Thomsen, Lars; Ristein, Jürgen; Pakes, Christopher I.; Fox, Neil A.; Ley, Lothar
Abstract : This paper reviews electron emission from negative electron affinity (NEA) diamond and gives account of the recent developments in alternatives to hydrogen‐termination for producing NEA diamond surfaces, particularly using lithium on oxygen‐terminated diamond. We discuss the background and motivation for using alkali metals and present both experimental and computational results that cover structure, electronic properties, photoemission, and total photoyield. Secondary yield enhancement of over 200 × is demonstrated over a reference surface with positive electron affinity. Abstract : One of the incredible properties of diamond is negative electron affinity: electrons excited in diamond can escape with no barrier to emission. In this Feature Article, the authors discuss a new way of generating negative electron affinity on diamond using lithium and present a summary of the work that was done to understand lithiated diamond surfaces.